Parameters for automated star identification - Balodis, Jānis; Zariņš, Ansis; Haritonova, Diāna; Janpaule, Inese (Geodesy and Cartography, 2014)
The determination of parameters for identifying stars sensed by charge-coupled device (CCD) is discussed. Numerical experiments are summarized which support the parameter space bound estimation practicality of the proposed star pattern recognition and identification by matching with coordinate list in star catalogue. The parameter analysis performed to apply them for proper identification algorithm which is developed and used at the Institute of Geodesy and Geoinformatics. This algorithm is applied for identification of large volume star sets.